Implementasi Pembelajaran PAI Berbasis Information, Communication and Technology di SMP Bengkulu - Nanik Nanik (GHAITSA : Islamic Education Journal, 2020)
Another factor that cannot be ignored in learning is involving students in the learning process. This study aims to describe the planning, implementation which includes (strategy, methods, materials, media, assessment), evaluation, as well as identifying obstacles and solutions to overcome obstacles in learning ICT-based Islamic Education at SMPN 1 Bengkulu. This research method is descriptive qualitative. Sources of data were obtained from places and events, informants, and documents. Places and events in the learning process took place at SMPN 1 Bengkulu. The informants are school principals, teachers of Islamic Religious Education subjects, curriculum division, facilities and infrastructure division, students, school supervisors, and parents of students. The documents studied are documents related to the implementation of Islamic Religious Education learning. The data were analyzed using an interactive analysis model which included data reduction, data presentation, and drawing conclusions/verification. Based on the results of the study, it can be concluded as follows, 1) The planning carried out by the teacher is in accordance with the KTSP. 2) Implementation of learning which includes active learning strategies, the methods used vary: lecture method, question and answer, inquiry and assignment, material: applying the law of reading qalqalah and ra, media: power point visualized via LCD, laptop, computer and internet, assessment : includes process assessment and results assessment with a computerized system that can be accessed via the SMS Gateway service. 3) Assessment of ICT-based learning is able to increase students' motivation and learning achievement, as well as being able to foster enthusiasm and passion for learning. 4) the obstacles in learning to use ICT media are the class is a bit crowded, nervous during presentations, there are children who don't have laptops, computers, modems, to access material from the internet, internet networks that sometimes don't connect. Solutions to overcome obstacles, given direction so that the class is conducive, guidance, fulfillment of infrastructure in each class.